2016
DOI: 10.1007/s10589-016-9837-x
|View full text |Cite
|
Sign up to set email alerts
|

On the global convergence of the inexact semi-smooth Newton method for absolute value equation

Abstract: In this paper, we investigate global convergence properties of the inexact nonsmooth Newton method for solving the system of absolute value equations (AVE). Global Q-linear convergence is established under suitable assumptions. Moreover, we present some numerical experiments designed to investigate the practical viability of the proposed scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Using the previous lemma, problem (1) can be replaced by a sequence of concave optimization problems for r > 0 :…”
Section: Ave As a Sequence Of Concave Minimization Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the previous lemma, problem (1) can be replaced by a sequence of concave optimization problems for r > 0 :…”
Section: Ave As a Sequence Of Concave Minimization Programsmentioning
confidence: 99%
“…In this study we put the variables in a compact set. Indeed, the functions θ r are more efficient when their arguments live in [0,1]. Besides, we use one way to express complementarity with Lemma 2.1 another way, which will be used in the numerical study, is to consider the following…”
Section: Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Saheya et al [31] focused on numerical comparisons based on four smoothing functions for (1.2). Bello Cruz et al [2] showed the global Q-linear convergence of the inexact semi-smooth Newton method for solving (1.2). Ke et al [10] studied a SOR-like iteration method for solving system of (1.2).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, some numerical methods have been developed to solve AVEs. These include the SLP method 5 , the semismooth Newton method and its inexact variants [6][7][8] , the sign accord method 9 , the hybrid algorithm 10 , the Picard-CSCS iteration method, and the nonlinear CSCSlike iteration method 11 . When A ∈ n×n is a non-Hermitian positive definite matrix, the Hermitian and skew-Hermitian splitting (HSS) iteration was first introduced by Bai et al 12 and extended in Ref.…”
Section: Introductionmentioning
confidence: 99%